New polyurethane nanocomposites based on soya oil - Mohammed, Issam Ahmed; Abd Khadir, Nurul Khizrien; Al-Mulla, Emad Abbas Jaffar (Japan Oil Chemists' Society, 2014)
New polyurethane (PU) nanocomposites were prepared from a dispersion of 0 - 5% montmorillonite (MMT) clay with isocyanate and soya oil polyol that was synthesized via transesterification of triglycerides to reduce petroleum dependence. FT-IR spectra indicate the presence of hydrogen bonding between nanoclay and the polymer matrix, whereas the exfoliated structure of clay layers was confirmed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Optical microscopy, mechanical and thermal analyses were done to investigate significant improvement of the nanocomposites. The results showed PU–3% nanoclay (NC) showed optimum results in mechanical properties such as tensile and flexural strength but the lowest in impact strength.